2014
DOI: 10.1002/2014gl059241
|View full text |Cite
|
Sign up to set email alerts
|

Cold electron heating by EMIC waves in the plasmaspheric plume with observations of the Cluster satellite

Abstract: We report in situ observations by the Cluster spacecraft of plasmaspheric electron heating in the plasmaspheric plume. Electron heating events were accompanied by enhancements of electromagnetic ion cyclotron (EMIC) waves in the increased density ducts on the negative density gradient side for two substructures of the plasmaspheric plume. Electron heating is much stronger for the pitch angle of 0°and 180°than for the pitch angle of 90°. Theoretical calculations of the Landau resonant interaction between electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 31 publications
1
56
0
1
Order By: Relevance
“…Through wave particle interaction, they can lead to precipitations of ring current ions [ Cornwall et al ., ; Jordanova et al ., ; Keika et al ., ; Yuan et al ., , ; Zhu et al ., ; Su et al ., ] and relativistic electrons [ Bortnik et al ., ; Summers et al ., ; Jordanova et al ., ; Shprits et al ., ; Su et al ., , , , ; Yuan et al ., ; Hyun et al ., ; D. D. Wang et al , ]. Through Landau damping, they can also heat cold electrons in the magnetosphere [ Zhou et al ., ] and plasmaspheric plume [ Yuan et al ., ]. Therefore, it is necessary to investigate the distribution characteristics of EMIC waves in the inner magnetosphere, especially the distribution function about L and magnetic local time (MLT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through wave particle interaction, they can lead to precipitations of ring current ions [ Cornwall et al ., ; Jordanova et al ., ; Keika et al ., ; Yuan et al ., , ; Zhu et al ., ; Su et al ., ] and relativistic electrons [ Bortnik et al ., ; Summers et al ., ; Jordanova et al ., ; Shprits et al ., ; Su et al ., , , , ; Yuan et al ., ; Hyun et al ., ; D. D. Wang et al , ]. Through Landau damping, they can also heat cold electrons in the magnetosphere [ Zhou et al ., ] and plasmaspheric plume [ Yuan et al ., ]. Therefore, it is necessary to investigate the distribution characteristics of EMIC waves in the inner magnetosphere, especially the distribution function about L and magnetic local time (MLT).…”
Section: Introductionmentioning
confidence: 99%
“…Some theoretical and observational studies hold the view that EMIC waves are easier to be generated when the hot anisotropic ions encounter the dense and cold plasmasphere [ Gary et al ., ; Yuan et al ., ; Liu et al , ]. Plasmaspheric plumes are also suggested to be a preferential structure where EMIC waves can be generated easily [ Yuan et al ., ]. On the other hand, some studies emphasize the pivotal role of the solar wind dynamic pressure in the generation of the EMIC waves [ Usanova et al ., , ; McCollough et al ., , ].…”
Section: Introductionmentioning
confidence: 99%
“…Since cold dense ions can lower instability threshold for EMIC waves [ Gary et al ., ], EMIC waves are usually generated near the magnetospheric equator and observed in the plasmapause or plasmaspheric plumes [ Anderson et al ., ; Yuan et al ., ; Chen et al ., ; Yuan et al ., ]. EMIC waves play an important role in the inner magnetospheric dynamics through wave‐particle interaction [ Jordanova et al ., ; Fok et al ., ; Yuan et al ., , ]. Due to resonant interaction with MeV electrons, EMIC waves can also lead to the precipitation of MeV electrons and be considered as the dominant contributor to the rapid loss of radiation belt electrons loss [e.g., Summers and Thorne , ; Bortnik et al ., ; Millan and Thorne , ; Ukhorskiy et al ., ; Shprits et al ., ; Yuan et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the whistler mode growth rate is modulated by the variation of the electron gyrofrequency and by the adiabatic changes to the electron distribution caused by ULF waves [ Coroniti and Kennel , ], which would lead to the modulation of the VLF waves. In addition, several studies have shown that oblique EMIC waves can have large enough parallel electric fields to produce a Landau resonance causing electron heating, which could provide the free energy for whistler mode wave growth [ Mauk and McIlwain , ; Thorne et al ., ; Yuan et al ., ]. The ULF waves have also been shown to modulate whistler mode waves sufficiently to account for precipitation signatures observed on the ground [ Watt et al ., ].…”
Section: Discussion and Future Workmentioning
confidence: 99%